Rational Development of Novel Activity Probes for the Analysis of Human Cytochromes P450. (6th May 2016) - Sellars, Jonathan D.; Skipsey, Mark; Sadr‐ul‐Shaheed; Gravell, Sebastian; Abumansour, Hamza; Kashtl, Ghasaq; Irfan, Jawaria; Khot, Mohamed; Pors, Klaus; Patterson, Laurence H.; Sutton, Chris W.
Abstract: The identification and quantification of functional cytochromes P450 (CYPs) in biological samples is proving important for robust analyses of drug efficacy and metabolic disposition. In this study, a novel CYP activity‐based probe was rationally designed and synthesised, demonstrating selective binding of CYP isoforms. The dependence of probe binding upon the presence of NADPH permits the selective detection of functionally active CYP. This allows the detection and analysis of these enzymes using biochemical and proteomic methodologies and approaches. Abstract : Tagged: you′re it ! The identification of functional cytochrome P450 (CYP) enzymes in primary tissues is important for the robust analysis of drug efficacy and metabolism. Herein we describe the synthesis of a novel CYP activity‐based probe, which demonstrates selective binding of human recombinant CYP isoforms.